A Rare Case of GATA2 Deficiency Presenting as Recurrent Fever in an Adult Man - Esmeralda Gutierrez-Asis; Neetu Mahendraker; Haley Pritchard (Annals of Internal Medicine: Clinical Cases)
A 36-year-old man with GATA2 immunodeficiency syndrome who had fever, weight loss, and pancytopenia was diagnosed with disseminated Mycobacterium xenopi infection. He was treated for infection and later diagnosed with myelodysplastic syndrome due to GATA2 deficiency. He recovered well after allogeneic hematopoietic stem cell transplant.